2015
DOI: 10.1088/1367-2630/17/7/073034
|View full text |Cite
|
Sign up to set email alerts
|

Magnus-induced ratchet effects for skyrmions interacting with asymmetric substrates

Abstract: We show using numerical simulations that pronounced ratchet effects can occur for ac driven skyrmions moving over asymmetric quasi-one-dimensional substrates. We find a new type of ratchet effect called a Magnus-induced transverse ratchet that arises when the ac driving force is applied perpendicular rather than parallel to the asymmetry direction of the substrate. This transverse ratchet effect only occurs when the Magnus term is finite, and the threshold ac amplitude needed to induce it decreases as the Magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…In previous numerical work, it was shown that an individual skyrmion in a 2D system interacting with a quasi-1D asymmetric substrate exhibits a rocking ratchet effect when the ac drive is applied along the substrate asymmetry direction 40 . In this case, the resulting dc skyrmion velocity has components both parallel and perpendicular to the substrate asymmetry direction due to the Magnus term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous numerical work, it was shown that an individual skyrmion in a 2D system interacting with a quasi-1D asymmetric substrate exhibits a rocking ratchet effect when the ac drive is applied along the substrate asymmetry direction 40 . In this case, the resulting dc skyrmion velocity has components both parallel and perpendicular to the substrate asymmetry direction due to the Magnus term.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the resulting dc skyrmion velocity has components both parallel and perpendicular to the substrate asymmetry direction due to the Magnus term. A new type of ratchet effect, called a Magnus ratchet, was shown to occur when the ac drive is applied perpendicular to the substrate asymmetry direction 40 . Here, the Magnus term induces skyrmion velocity components both parallel and perpendicular to the ac drive.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that, for a driving force with a specific frequency, e.g., m, if one assumes that the an excited mode of D is at frequency, e.g., q, then a series of frequencies of the skyrmion coordinate R will be excited, including m, |m+q|, |m-q|, |m+2q|, |m-2q|, …. The In Table I, We emphasize that the ratchet effect revealed in this work should be distinguished in both the source application and the dynamics behind from those driven by oscillating driving forces as reported in previous works [33][34][35][36][37] . The ratchet motion, either driven by a biased oscillating magnetic field 33 or by oscillating drives in combination with substrate asymmetry 35,36 , is intrinsically due to a spatial symmetry-breaking, as introduced by the field or by the substrate.…”
Section: E Discussionmentioning
confidence: 60%
“…The In Table I, We emphasize that the ratchet effect revealed in this work should be distinguished in both the source application and the dynamics behind from those driven by oscillating driving forces as reported in previous works [33][34][35][36][37] . The ratchet motion, either driven by a biased oscillating magnetic field 33 or by oscillating drives in combination with substrate asymmetry 35,36 , is intrinsically due to a spatial symmetry-breaking, as introduced by the field or by the substrate. For the ratchet motion driven by a tilted oscillating magnetic field 34 , while the dissipation force should also play an important role in the net motion, such a net dissipation force relies on the co-excitation of the gyration mode caused by the in-plane field and the breathing mode caused by the out-of-plane field.…”
Section: E Discussionmentioning
confidence: 60%
“…The relation between skyrmion and superconducting vortices was explored by Reichhardt et al [20] while Lin et al [21] treated the effects of a current pulse in the creation of a skyrmion. Reichhardt et al explored various aspects of skyrmion dynamics: effects of random quenched disorder [22], ac driven skyrmions over asymmetric quasi-one-dimensional substrates [23] and two-dimensional periodic substrates [24]. The effects of a small hole in a magnetic layer were explained by Muller and Rosch [25].…”
Section: Introductionmentioning
confidence: 99%